Race at predominantly White independent schools : the space between diversity and equity - French, Bonnie E. (Lanham : Lexington Books, 2018)
In Race at Predominantly White Independent Schools, Bonnie E. French investigates the management of "diversity" at predominantly White, independent schools in the northeastern United States. By conducting in-depth interviews with diversity policy developers and implementers within the independent school community, French explores current efforts toward racial equity and the relationship between racial equity and diversity. Data collected from interviews are supplemented with numerical data from the National Association of Independent Schools that chronicles enrollment and employment of people of color, as well as with content analysis of published materials from the independent school community. Using Critical Race Theory to frame this critique, French argues that the diversity movement, by not seeking to challenge the current state of inequality in a meaningful way, only serves to strengthen the segregated and unequal status quo. -- Provided by publisher.
A vision of diversity: who's on campus -- Financing the vision -- Embracing diversity: diversity programming on campus -- The meaning of diversity -- Evidence of continued racism -- An exception.
Includes bibliographical references and index.
Keywords: Racism in education -- United States; Private schools -- United States; Educational equalization -- United States